Effect of taro (Colocasia esculenta)foliage on the performance of growing common ducks - Tuyet Giang, Nguyen (2010)
Two on-farm experiments were carried out in An Giang Province, Vietnam, to investigate the effect of diets of rice bran with taro (Colocasia esculenta) foliage on the growth performance of common ducks.